The impact of change in physical activity on change in arterial stiffness in overweight or obese sedentary young adults. (August 2014) - Hawkins, Marquis; Gabriel, Kelley P; Cooper, Jennifer; Storti, Kristi L; Sutton-Tyrrell, Kim; Kriska, Andrea
Arterial stiffness is associated with cardiovascular events and mortality. Lifestyle factors such as physical activity (PA) may reduce arterial stiffness. The purpose of this study is to determine the impact of change in PA on 1-year change in arterial stiffness in 274 overweight/obese sedentary young adults. The Slow Adverse Vascular Effects of excess weight (SAVE) trial was a study evaluating the relationships between weight loss, dietary sodium, and vascular health. PA was measured with the ActiGraph AM7164 accelerometer. Intensity of activity was determined using established cut-points. Arterial stiffness was assessed by brachial–ankle pulse wave velocity (baPWV) using an automated device. Analysis of covariance compared changes in total accelerometer counts, minutes/day in light-intensity PA (LPA), moderate-to-vigorous PA (MVPA), and sedentary time, by categories of change in baPWV. Models were adjusted for time since baseline visit, age, sex, race, homeostatis model of assessment of insulin resistance, mean arterial pressure, heart rate, and weight change. Total accelerometer counts and time spent in MVPA increased from baseline to 12 months while time spent in LPA significantly decreased. Mean baPWV was similar at each time point. Those who showed decreased baPWV also showed an increase in total accelerometer counts per day and time spent in MVPA in the fully adjusted models ( p <0.001). Changes in sedentary time and time spent in LPA were not associated with changes in baPWV. These results indicate that even modest increases in MVPA can reduce arterial stiffness, a risk factor for future cardiovascular events.